A Critical Appraisal on Controlled Drugs: Classification, Global Regulatory Provisions, and Distribution - Ranjan, Animesh; Gaurav; Patil, Niraj Sandeep; Shashi, Shivendu Shekhar; Singh, Dilpreet (Current Indian Science, 2023)
Controlled drugs, characterized by their potential for abuse and addiction, require stringent regulation to ensure their safe and appropriate use. This critical appraisal provides a scientifically sound examination of the classification of controlled drugs, global regulatory provisions governing their use, and the challenges associated with their distribution. Due to poor regulation, it is anticipated that 80% of the world’s population will have insufficient access to these painkillers. India needs a more robust enforcement mechanism, with the main goal of ensuring that medications are accessible to patients in need while preventing abuse and trafficking. As a result, studying the topic of “A Regulatory Need of Controlled Drugs” is important, serious, and indispensable. As a result, the authors of the present review discussed numerous regulatory authorities, drug enforcement agencies, and the storage and distribution of banned substances in India. In light of the findings, this review suggests future directions and recommendations. Strengthening international collaboration and information sharing can facilitate the development of more effective regulatory measures. Improved tracking and monitoring systems, incorporating technological advancements, hold promise for enhancing control over the distribution of controlled drugs.
Keywords: Regulation